Detection of Zika virus RNA in semen of asymptomatic blood donors. (December 2017) - Musso, D.; Richard, V.; Teissier, A.; Stone, M.; Lanteri, M.C.; Latoni, G.; Alsina, J.; Reik, R.; Busch, M.P.; ,
Abstract: Objectives: Zika virus (ZIKV) transmission through semen donation has never been reported but the risk is supported by the detection of ZIKV in semen and the demonstration of ZIKV sexual transmission. The potential impact of ZIKV on assisted reproductive procedures should be evaluated. Methods: We tested longitudinally collected semen samples provided by asymptomatic blood donors who tested positive for ZIKV RNA in plasma during ZIKV outbreaks in Puerto Rico and Florida in 2016. Results: Five of the 14 (35.7%) asymptomatic blood donors provided semen samples that tested positive for ZIKV RNA, with ZIKV RNA loads ranging from 8.03 × 10 3 to 2.55 × 10 6 copies/mL. Plasma collected at the same time as the semen tested negative for ZIKV RNA for most ZIKV RNA-positive semen collections; all corresponding plasma samples tested positive or equivocal for anti-ZIKV IgG antibodies and all except one tested positive for ZIKV IgM antibodies. The rate of detection of ZIKV RNA in semen in asymptomatic donors is not significantly different from the rate previously reported for symptomatic patients. Conclusions: Our results that show a high percentage of detection of ZIKV RNA in the semen of asymptomatic men confirm that ZIKV is a new threat for reproductive medicine and should have important implications for assisted reproductive technology. We recommend that semen donations from men at risk for ZIKV infection should be tested for ZIKV RNA, regardless of symptoms of ZIKV infection.